Peran Motivasi Guru PAI dalam Peningkatan Kedisiplinan Siswa di SD Al-Husainiyyah Bandung - Lina Erliana; Helmi Aziz; Sobar Al Ghazal (Bandung Conference Series: Islamic Education, 2022)
Abstract. Islamic education is one of the basic sciences that plays an important role in shaping the character of the mindset and behavior of students. Initial observations made at SD Al-Husainiyyah Bandung became the basis that it turned out that there were several problems with regard to student discipline. The reality showed a tendency such as some students not doing homework or assignments. Therefore PAI teachers or classroom teachers are required to motivate students in discipline and encourage children to apply disciplined attitudes. Based on this phenomenon, the problem in this research is formulated "What is the role, what should be done in increasing motivation, how are the supporting and inhibiting factors of discipline". Furthermore, the objectives in this study are described in the following points: (1) to be able to reveal how efforts are made to improve student discipline at Al-Husainiyyah Elementary School, (2) to analyze how the role of PAI teachers in improving student discipline at SD AL-Husainiyyah Husainiyyah, (3) to determine the supporting and inhibiting factors of discipline in Al-Husainiyyah Elementary School. The researcher used qualitative descriptive method. The data sources used are primary data sources, namely teachers of Islamic education subjects at Al-Husainiyyah Elementary School Bandung and secondary data sources in the form of documents. With data collection techniques, namely interviews, observations. Conducting interviews with teachers of Islamic religious education subjects at SD Al-Husainiyyah Bandung. The data analysis techniques used in this study were data reduction, data presentation. The results of this study: that the PAI teacher's efforts to improve discipline are by providing understanding and understanding, the supporting supporting factors are that the students have received new knowledge and are easy to apply and the inhibiting factor is that there are still some students who are lazy so that they do not discipline. Abstrak. Penddikan Agama Islam merupakan salah satu ilmu dasar yang memegang peranan penting dalam pembentukan karakter pola pikir dan tingkah laku siswa. Pengamatan awal yang dilakukan di SD Al-Husainiyyah Bandung menjadi dasar bahwa ternyata terdapat beberapa masalah berkenaan dengan kedisiplinan siswa.Kenyataan menunjukan kecenderungan seperti sebagian siswa tidak mengerjakan pekerjaan rumah atau tugas. Oleh karena itu guru PAI atau guru kelas dituntut untuk memotivasi siswa dalam kedisiplinan dan mendorong anak-anak untuk menerapkan sikap disiplin.. Berdasarkan fenomena tersebut, maka permasalahan dalam penelitian ini dirumuskan “ Bagaimana peran, Apa yang harus dilakukan dalam meningkatkan motivasai, bagaimana faktor pendukung dan penghambat dari kedisiplinan “. Selanjutya, tujuan dalam penelitian ini di uraikan dalam pokok-pokok sebagai berikut: (1) untuk apat mengungkapkan bagaimana upaya dalam meningkatkan kedisiplinan siswa di SD Al-Husainiyyah, (2) untuk menganalisis bagaimana peran guru PAI dalam menigkatkan kedisiplinan siswa di SD AL-Husainiyyah, (3) untuk mengetahui faktor pendukung dan penghambat dari kedisiplinan di SD Al-Husainiyyah. Peneliti menggunakan metode deskriptif kualitataif. Adapun sumber data yang digunakan adalah sumber data primer yaitu guru mata pelajaran pendidikan Agama Islam SD Al-Husainiyyah Bandung dan data sumber sekunder berupa dokumen. Dengan teknik pengumpulan data yaitu waawancara, observasi. Melakukan wawancara dengan guru mata pelajaran pendidikan agama Islam SD Al-Husainiyyah Bandung. .Adapun teknik analisis data yang digunakan dalam penelitian ini adalah redukasi data, penyajian data. Hasil dari penelitian ini: bahwa upaya guru PAI dala menngkatkan kedisiplinan ialah dengan memberikan pengertian dan pemahaman, faktor pendukung pendukung ialah para siswa udah dalam menerima pengerahuan yang baru serta mudah dalam pengaplikasiannyapun dan faktor pnghambat ialah masih ada beberapa siswa yang bermalas-malasan sehingga ia tidak disiplin.